Phenotypic response of farmer-selected CWR-derived rice lines to salt stress in the Mekong Delta - Tin, Huynh Quang; Loi, Nguyen Huu; Labarosa, Sandy Jan E.; McNally, Kenneth L.; McCouch, Susan; Kilian, Benjamin (Wiley, 2021)
Breeding for salt tolerance or abiotic stress, in general, requires rapid but reliable screening protocols that reflect the actual field situation as much as possible. A collection of 200 crop wild relative (CWR)‐derived BC3F3‐4 rice (Oryza sativa L.) lines developed at the International Rice Research Institute (IRRI) were evaluated by farmers in the Mekong Delta over two seasons for agronomic performance. Fifty stable BC3F5 lines were selected and subsequently screened in hydroponics using three NaCl concentrations to assess their phenotypic response to salt stress. The lines and check varieties were grown in a salinized Yoshida nutrient solution at three concentrations: 68, 102, and 13 mM NaCl. Several lines were identified to be tolerant to salinity stress and ANOVA showed significant differences among genotypes and NaCl concentrations. Root and shoot growth parameters showed an inverse relationship with increasing NaCl concentration. Population genetic analysis suggested four groups of genotypes, where the median salt injury score across the three NaCl concentrations was identified as the main clustering factor. Lines from Cluster 3 were identified as the most promising donors of salt tolerance.